Rare cause of severe hematemesis due to IgG4-related gastric ulcer - Yu-Qin He; Xin Fu; Dong-Feng Chen; Dong-Feng Chen (Turkish Journal of Gastroenterology, 2019)
Cite this article as: He YQ, Fu X, Chen DF. Rare cause of severe hematemesis due to IgG4-related gastric ulcer. Turk J Gastroenterol 2019; 30(10): 925-7.